Pembuatan mikrokristalin selulosa dari wortel (Daucus carota L.) dengan avicel PH 102 sebagai pembanding dan evaluasi mutu fisik - Chairina Milda; Gabena Indrayani Dalimunthe; Minda Sari Lubis; Rafita Yuniarti (Journal of Pharmaceutical and Sciences, 2023)
Carrots (Daucus carota L.) are vegetable types of annuals because they only produce once and then die. Carrot tubers are reddish-yellow due to the high content of carotene. Microcrystalline cellulose is one of the excipients (additives) in tablet preparations, namely as a filler, which is considered a binding agent because it can increase the compactness ability of tablets from compression mixtures. Microcrystalline cellulose comes from natural resources containing lignocellulose fibers such as wood and non-wood. One of the abundant fibrous plants in Indonesia is carrots (Daucus carota L.). The main chemical composition of carrots includes carbohydrates, namely dietary fiber (hemicellulose, cellulose), starch, and several types of sugar. This research aimed to determine whether carrot cellulose (Daucus carota L.) can be made into microcrystalline cellulose and compare the physical quality of carrot cellulose microcrystalline results with Avicel PH 102. Microcrystalline cellulose is made by a delignification process using 15% NaOH, followed by a bleaching process using 3.5% NaOCl, and then continued with a hydrolysis process with HCl 2.5N. Then, microcrystalline cellulose is carried out a physical quality evaluation, which includes organoleptic, identification, pH, solubility of substances in water, shrinkage of dryers, and starch. The results of the research showed that carrots can be made into microcrystalline cellulose, namely with the results of physical quality evaluation compared to Avicel PH 102, organoleptic powder, odorless, tasteless, and yellowish white (microcrystalline cellulose) and white (Avicel PH 102); identification, each of which produces a blue-violet color; pH 5.67 and 6.5; the solubility of substances in water is 0.1% each; drying shrinkage 4.70% and 2.53%; and starch, respectively not formed violet blue solution.